SCREENING TESTS FOR THYROID DYSFUNCTION; IS TSH SUFFICIENT? Received: 17th July 2021; Revised: 31st July 2021, 11th November 2021; Accepted: 13th November 2021 - Minxuri, Dorina; Mitre, Anila; Bino, Silva; Kostrista, Entela; Hysaj, Kejsi (LIFE: International Journal of Health and Life-Sciences, 2021)
There are different recommendations on how to screen for thyroid gland problems and TSH is the most ordered test. Anti TPO antibodies are usually tested when TSH is not within the normal range, but their presence before TSH changes has not been appreciated. This study aims to evaluate the role of anti-TPO and thyroid ultrasound for the early detection of thyroid pathologies, especially in the subclinical phase. This is a cross-sectional study in 458 individuals (80% females and 20% males). Thyroid laboratory tests and thyroid ultrasound was done. Statistical analysis was performed to assess the prevalence of thyroid dysfunction, thyroid antibodies and their correlation with thyroid ultrasound changes. 88.6 % (406) of subjects resulted in euthyroid. Subclinical hypothyroidism and hyperthyroidism were observed in 5.5% and 1.7% of the population, respectively. The prevalence of positive thyroid antibodies was 26.5% in females and 11.8 % in males. Hypoechoic structure, heterogenicity and micronodular pattern in ultrasound were associated with significantly higher TPO antibodies activity p<.001. Undiagnosed biochemical thyroid dysfunctions were common in our country. Measurement of anti-TPO in individuals with normal TSH is valuable in determining individuals at risk for thyroid pathologies.